An Overview of the Quality of Outpatient Administrative Registration Service at Pengayoman Cipinang Hospital Jakarta in 2025 - Anggareini, Marshella; Harahap, Sarah Geltri; Juliani, Enni (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2026)
Outpatient registration administration services are the first gateway to interaction between patients and hospitals. This study aimed to analyze the quality of outpatient registration administration services at Pengayoman Cipinang Hospital in 2025 based on hospital service standards, focusing on four key aspects: availability, responsiveness, comfort, and timeliness. The approach used was descriptive quantitative, with a sample of 42 outpatient respondents who met the criteria. Data were collected using a Likert-based questionnaire instrument, then analyzed to describe respondents' perceptions of the four service dimensions. The analysis results showed that the majority of patients gave a positive assessment of service quality, with the highest percentage in the comfort dimension (76.2%), followed by punctuality (75.5%), availability (74.4%), and responsiveness (70.24%). These findings indicated that although the service system has been running quite effectively, there are still gaps for improvement to achieve excellent service standards. Recommendations proposed include optimizing the number of service counters during peak hours, conducting regular training for administrative staff, improving waiting room facilities, and implementing a digital information system capable of providing real-time queue status updates to patients. These efforts are expected to maintain the existing quality of administrative registration services at Pengayoman Cipinang Hospital.